2016
DOI: 10.3389/fpsyg.2016.02012
|View full text |Cite
|
Sign up to set email alerts
|

Income and Well-Being: Relative Income and Absolute Income Weaken Negative Emotion, but Only Relative Income Improves Positive Emotion

Abstract: Whether relative income or absolute income could affect subjective well-being has been a bone of contention for years. Life satisfaction and the relative frequency of positive and negative emotions are parts of subjective well-being. According to the prospect theory, hedonic adaptation helps to explain why positive emotion is often so hard to be maintained, and negative emotion wouldn’t be easy to be eliminated. So we expect the relationship between income and positive emotion is different from that between in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 25 publications
5
19
1
2
Order By: Relevance
“…Our results confirmed that higher monthly income was related to better outcomes on all psychosocial outcome measures. This finding substantiates the anticipated close relationship between psychological wellbeing and poverty, consistent with the findings of previous studies (Arendt, 2005;Camfield & Esposito, 2014;Yu & Chen, 2016), indicating that higher income could help people overcome difficult circumstances including hunger and cold that may negatively affect their subjective wellbeing. Moreover, money leads to increased happiness if it can be exchanged for goods that will improve an individual's utility and general social rank (Boyce, Brown, & Moore, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…Our results confirmed that higher monthly income was related to better outcomes on all psychosocial outcome measures. This finding substantiates the anticipated close relationship between psychological wellbeing and poverty, consistent with the findings of previous studies (Arendt, 2005;Camfield & Esposito, 2014;Yu & Chen, 2016), indicating that higher income could help people overcome difficult circumstances including hunger and cold that may negatively affect their subjective wellbeing. Moreover, money leads to increased happiness if it can be exchanged for goods that will improve an individual's utility and general social rank (Boyce, Brown, & Moore, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…In the same vein, future research would consider that parental economic socialization should interact with emotions or other individual features (Rodríguez et al, 2015 ; Yu and Chen, 2016 ) or personality characteristics (Topa and Herrador-Alcaide, 2016 ) in order to affect retirement planning.…”
Section: Discussionmentioning
confidence: 99%
“…Income most likely affects how we perceive our global life circumstances as it is something that we often consider when judging how our overall life is going, while its impact on what we experience on a daily basis may be more limited, especially if we take hedonic adaptation into account, i.e. the human tendency to easily get used to new situations and standards of living (Yu and Chen 2016). Moreover, income can be assumed to increase life's comforts and to help us fulfil our desires, but may be less efficient in fulfilling our fundamental psychological needs such as connectedness, autonomy and competence, whereas the latter has been found to be more closely related to emotional wellbeing (Scitovsky 1978;Diener et al 2010).…”
Section: Affectmentioning
confidence: 99%